A study of Singapore adolescent girls' selfie practices, peer appearance comparisons, and body esteem on Instagram. (June 2019) - Chang, Leanne; Li, Pengxiang; Loh, Renae Sze Ming; Chua, Trudy Hui Hui
Highlights: Girls' selfie practices, peer appearance comparisons, and body esteem were examined. Selfie practices were examined as selfie browsing, posting, and editing. Selfie posting was directly and positively associated with body esteem. Appearance comparisons mediated the paths from browsing and editing to body esteem. Direction of appearance comparisons did not moderate the mediating process. Abstract: Social media allow users to play multiple roles as receivers, exhibitors, and evaluators of idealized images through photo browsing, posting, and editing. In this study, we examined the associations between adolescent girls' various types of Instagram selfie practices and their body esteem. The mediating role of appearance comparisons and the moderating role of direction of comparisons were also tested. A survey was distributed to 303 adolescent girls from three secondary schools in Singapore. Results indicated that the negative associations between participants' photo browsing and editing behaviors and body esteem were fully mediated by peer appearance comparisons. Contrarily, selfie posting had a direct and positive association with body esteem that was not mediated by peer appearance comparisons. The findings suggested that objectifying standards of beauty may permeate adolescent girls' value systems through frequent appearance comparisons on social media. When peer influence was presented in the form of appearance comparisons, it had a strong negative association with body esteem, regardless of the direction of the comparisons involved. The positive relationship between selfie posting and body esteem suggested that peer interactions may benefit adolescent girls' body image development in specific ways that warrants further inquiry.